The Impact of the Russia-Ukraine War on the Economy of the European Union - Tsotne Chachanidze (International Society of Philosophy and Cosmology, 2023)
The European Union has reacted to the war on its eastern border with remarkable unity, resolve, and speed. However, the invasion of Ukraine is a watershed moment. Regardless of how long the war lasts, its legacy will be long-lasting. It will shape Europe's policy choices in the coming years and decades. This article attempts to provide a preliminary assessment of the economic policy implications of the invasion and actions made since February 24, when Russian forces entered Ukraine. The major immediate concerns to the European economy include supply shocks caused by rising oil and gas prices, Europe's reliance on Russian energy, and the impact of geopolitical uncertainties on consumer confidence and investor mood. Europe must also welcome millions of war refugees and give them with emergency aid. Longer term, they confront a total rethinking of the EU policy structure, affecting budgetary priorities, macroeconomic policy principles, market regulation, and the allocation of responsibility between the EU and its member states. Many more pathways are ignored for the purposes of this article, ranging from the confidence shock to the rippling effects on agricultural supplies and commodity markets.